Tingkat Pengetahuan Pemirsa tentang Iklan Kesehatan "Cuci Tangan" di Televisi (Studi Deskriptif Tingkat Pengetahuan Pemirsa tentang Iklan Kesehatan "Cuci Tangan" di Televisi) - Saifuddin Zuhri (Jurnal Aplikasi Manajemen, 2010)
These days, universalize Indonesian advertising amends. Advertising expense by business world also tend to always increase from rime to time. Increasing it that advertising expense proves that industrial circle stills to give trust to advertisers to promote its product. Advertisement is process forwarding of information or message to some of or all by using media. One of the media to submit message in the form of advertisement is television. Basis for theory which is utilized deep observational it is advertising existence history al society, advertising, advertising basic principles, television as media of advertising, television as advertisement media. television as communications media. health communicattons, effective communications, beholder as all people, knowledge, advertisement clean hand, and theory of SOR. Method Research use descriptively. Data processing obtained from result of kuesioner; hereinafter analysed descriptively. Population in this research is society of Surabaya. Technique determination of sample use formula of Yamane and technique withdrawal of sample is purposive sampling. Result of research can concluded that most responder included in high category. Because inquiring had big responder when seeing health advertisement "Clean Hand" looked up and down so that responder know advertisement of health "Clean Hand". Besides also there are included in responder category. Because responder see health advertisement "Clean Hand" only just part so that mount owned knowledge it.